The Odd Generalized Exponential Type-I Generalised Half Logistic Distribution: Properties and Application (International Journal of Engineering and Computer Science, 2018)
We propose a new lifetime model, called the Odd Generalized Exponential Type-I Generalised Half Logistic Distribution (OGET-IGHLD).We obtain some of its mathematical properties. We made an attempt to study some structural properties of the new distribution. The Maximum Likelihood method is used for Estimating the model parameters and the Fisher’s information matrix is also derived. We illustrate the  applications with generalised data.